2004
DOI: 10.1016/j.laa.2004.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Factorization of J-unitary matrix polynomials on the line and a Schur algorithm for generalized Nevanlinna functions

Abstract: We prove that a 2 × 2 matrix polynomial which is J -unitary on the real line can be written as a product of normalized elementary J -unitary factors and a J-unitary constant. In the second part we give an algorithm for this factorization using an analog of the Schur transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…In the indefinite case the above recursion algorithm was studied by Derevyagin in 10 and the formula (4.19) for the matrix W (λ) with the statement of the theorem for the nondegenerate even moment problem has been proven in 11. The linear fractional transformation similar to \documentclass{article}\usepackage{amssymb}\begin{document}\pagestyle{empty}${\mathcal T}_j$\end{document} (the so‐called Schur transform) has been studied by Alpay, Dijksma, and Langer in 3, 4.…”
Section: Schur Algorithmmentioning
confidence: 99%
“…In the indefinite case the above recursion algorithm was studied by Derevyagin in 10 and the formula (4.19) for the matrix W (λ) with the statement of the theorem for the nondegenerate even moment problem has been proven in 11. The linear fractional transformation similar to \documentclass{article}\usepackage{amssymb}\begin{document}\pagestyle{empty}${\mathcal T}_j$\end{document} (the so‐called Schur transform) has been studied by Alpay, Dijksma, and Langer in 3, 4.…”
Section: Schur Algorithmmentioning
confidence: 99%
“…In [3] it was shown that each J-unitary polynomial matrix on R admits a factorization of the form (3.90) with somewhat different elementary factors W j (λ). In [3] it was shown that each J-unitary polynomial matrix on R admits a factorization of the form (3.90) with somewhat different elementary factors W j (λ).…”
Section: Corollary 324 Every Polynomial Matrix Satisfying Conditionmentioning
confidence: 99%
“…Given ,κ,kdouble-struckZ+, and a sequence s={}sjj=0 of real numbers, describe the set scriptMκkfalse(boldsfalse) of functions fboldNκk, which satisfy the asymptotic expansion ffalse(zfalse)=s0zsz+1+o1z+1false(z=iy,0.16em0.16emyfalse).Such a moment problem is called even or odd regarding to the oddness of the number +1 of given moments. To study this problem we use the Schur algorithm, which was elaborated in , and for the class Nκ. Applications of the Schur algorithm to degenerate moment problem in the class Nκ were given in .…”
Section: Introductionmentioning
confidence: 99%
“…To study this problem we use the Schur algorithm, which was elaborated in [5], [6] and [2] for the class N κ . Applications of the Schur algorithm to degenerate moment problem in the class N κ were given in [10].…”
Section: Introductionmentioning
confidence: 99%